2021
DOI: 10.1007/s10668-021-01465-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of municipal solid waste management system in Lae City, Papua New Guinea in the context of sustainable development

Abstract: Lae City (LC) of Morobe Province is the second-largest city in Papua New Guinea. Due to the abundant natural resources it inherits, the resultant urbanization has led to an influx of the human population. This increase in population as a result of industrialization has led to increased municipal solid waste (MSW) accumulation. To address this exigent issue, which affects the nation’s carbon footprint, it is imperative to review socio-economic and geographic factors to establish a feasible approach for managing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Incineration offers better potential for reducing GHG emissions than gasification or anaerobic digestion since it can process a bigger volume of waste and generate more energy [29]. By tightening restrictions and implementing the provided waste reduction route, MSW disposal at the designated garbage landfill may be decreased [30]. The debt-to-income ratio promotes MSW growth, but the debt-to-output ratio restrains it.…”
Section: H1mentioning
confidence: 99%
“…Incineration offers better potential for reducing GHG emissions than gasification or anaerobic digestion since it can process a bigger volume of waste and generate more energy [29]. By tightening restrictions and implementing the provided waste reduction route, MSW disposal at the designated garbage landfill may be decreased [30]. The debt-to-income ratio promotes MSW growth, but the debt-to-output ratio restrains it.…”
Section: H1mentioning
confidence: 99%
“…Ten years later, the per capita waste generation increased to 1.2 kg/p/d for about 1.3 billion urban residents, and it has been estimated that by the year 2025, about 4.3 billion urban residents will have an average generation rate of about 1.42 kg/p/d for solid waste [ 1 ]. However, the waste characteristics varies according to the source activity [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Doaemo et al [24] suggested 3 core waste management hierarchy systems to support sustainable development for Lae City by reviewing existing opportunities and challenges associated with the current municipal solid waste management system and the associated policies. The result shows that a zero waste campaign for resource recovery involving all stakeholders can be implemented since the organic content of municipal solid waste generated in Lae City reaches 70%.…”
Section: Introductionmentioning
confidence: 99%